2020
DOI: 10.1002/jor.24920
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes of frozen shoulder in rat model and the therapeutic effect of PPAR‐γ agonist

Abstract: Frozen shoulder is a common shoulder disorder characterized by a gradual increase of pain and a limited range of motion. However, its pathophysiologic mechanisms remain unclear and there is no consensus as to the most effective treatment. The purpose of the study was to investigate the effect of transforming growth factor-β (TGF-β) on fibrosis and inflammatory response of the shoulder joint of rat models and to explore the therapeutic effect of the peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Similar to these data, we demonstrate that IL-17A can directly promote a number of profibrotic mechanisms, including fibroblast survival and enhanced gene expression of proteins associated with matrix deposition. These profibrotic characteristics have previously been attributed to the elevated levels of the cytokine TGF-β in frozen shoulder ( 12 , 14 , 56 ). However, our data suggest the presence of IL-17A can also encourage the fibrotic hallmarks of frozen shoulder.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar to these data, we demonstrate that IL-17A can directly promote a number of profibrotic mechanisms, including fibroblast survival and enhanced gene expression of proteins associated with matrix deposition. These profibrotic characteristics have previously been attributed to the elevated levels of the cytokine TGF-β in frozen shoulder ( 12 , 14 , 56 ). However, our data suggest the presence of IL-17A can also encourage the fibrotic hallmarks of frozen shoulder.…”
Section: Discussionmentioning
confidence: 88%
“…Although a number of animal models have been used to study cytokine-driven fibrotic pathogenesis, there is no well-described in vivo model available for frozen shoulder. Those that have described in vivo models have tended to inject TGF-β ( 56 ) into the joint or use joint immobilization ( 61 ) to directly explore the fibrotic pathways more so than the inflammatory mechanisms of disease, which may result in fibrosis. Additionally, in the current study, we primarily measure gene expression of matrix proteins rather than the physical proteins following IL-17A exposure.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, driven by inflammation, a large number of fibroblasts are recruited in the shoulder capsule, and then secrete a large amount of collagen, leading to stiffness [ 10 , 12 , 13 ]. Therefore, promoting collagen degradation or inhibiting the secretion of collagen by fibroblasts has become the focus of anti-fibrosis for SS.…”
Section: Discussionmentioning
confidence: 99%
“…Triggered by inflammation, SS is characterized by thickening, stiffening, and fibrosis of joint capsule [ 9 , 10 ]. Numerous treatments were proposed against inflammation [ [11] , [12] , [13] ]. For example, Sun et al reported that steroid injection was effective against SS in inflammatory stage [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vimentin, TNF‐α, IL‐1β collagen 1 (COL1), and collagen 3 (COL3) are key effectors of FS pathogenesis and development. The peroxisome proliferator-activated receptor gamma (PPAR‐γ) agonist rosiglitazone was recently demonstrated to alleviate FS pathogenesis through these cytokines down regulation of [ 19 ]. Salmon calcitonin (sCT), a new candidate drug through its high ability to stimulate calcitonin receptor, activates protein kinase C (PKC) and protein kinase A (PKA) that are responsible for the down-regulation of fibrosis‐related molecules such as collagen 1, collagen 3, TGF‐β1, and interleukin-1α [ 20 ].…”
Section: Reviewmentioning
confidence: 99%